Respuesta :
Answer:
A = -120
AX = -240
X = 2
Step-by-step explanation:
∵ x + 4y - z = -14
∵ 5x + 6y + 3z = 4
∵ -2x + 7y + 2z = -17
[tex]\left[\begin{array}{ccc}1&4&-1\\5&6&3\\-2&7&2\end{array}\right]=\left[\begin{array}{ccc}-14\\4\\-17\end{array}\right][/tex]
∴ A = 1(6×2 - 3×7) + (-4)(2×5 - 3×-2) + (-1)(5×7 - 6×-2)
∴ A = 1(12 - 21) + (-4)(10 - -6) + (-1)(35 - -12)
∴ A = -9 + (-4)(16) + (-1)(47) = -9 - 64 - 47 = -120
To find X replace the column of X by the column of the answer
[tex]\left[\begin{array}{ccc}-14&4&-1\\4&6&3\\-17&7&2\end{array}\right][/tex]
∴ AX = -14(6×2 - 3×7) + (-4)(4×2 - 3×-17) + (-1)(4×7 - 6×-17)
∴ AX = -14(12 - 21) + (-4)(8 - -51) + (-1)(28 - -102)
∴ AX = 126 + (-4)(59) + (-1)(130) = 126 - 236 - 130 = -240
∴ X = AX/A = -240/-120 = 2
From the given three equations, we have;
- A = -120
- AX = -240
- X = 2
How can Cramer's rule be used to find X?
The given linear systems of equations are presented as follows;
x + 4•y - z = -14
5•x + 6•y + 3•z = 4
-2•x + 7•y + 2•z = -17
Which gives;
- A = 1×(6×2-3×7) + 4×((5×2) - 3×(-2)) + (-1)×(5×7-6×(-2)) = -120
AX is found as follows;
Substituting the first row, with the right side of the equation, we have;
-14 + 4•y - z
4 + 6•y + 3•z
-17 + 7•y + 2•z
- AX = -14×(6×2-3×7) + 4×((4×2) - 3×(-17)) + (-1)×(4×7-6×(-17)) = -240
X = AX/A
Which gives;
X = -240/(-120) = 2
Learn more about linear systems of equations here:
https://brainly.com/question/11637584